2007
DOI: 10.1080/10476210701325176
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Instruction in an Online Graduate Education Course

Abstract: Computer-mediated distance education holds potential for providing professional development opportunities for teachers. This study investigated teaching and learning through written asynchronous and synchronous communications in an online graduate education course. Types of student participation during four weeks of discussions in the course, two weeks involving discussion boards (asynchronous) and two involving chat sessions (synchronous), were analyzed to better understand the instruction and learning taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…In many studies, the qualitative data were quantified for analysis and presentation of the findings (Ahern & El-Hindi, 2000;Brooks & Bippus, 2012;Fernandez, 2007;Huang & Nakazawa, 2010;Lapadat, 2007;Maushak & Ou, 2007;Pilkington & Walker, 2003;Thomas, 2002;Xie & Ke, 2011); however, only one mixed-methods study (Exter et al, 2009) was found during the search, indicating a potential direction for future research. In many recent studies, social network analysis was applied to generate findings from a new perspective.…”
Section: Methods Appliedmentioning
confidence: 99%
See 4 more Smart Citations
“…In many studies, the qualitative data were quantified for analysis and presentation of the findings (Ahern & El-Hindi, 2000;Brooks & Bippus, 2012;Fernandez, 2007;Huang & Nakazawa, 2010;Lapadat, 2007;Maushak & Ou, 2007;Pilkington & Walker, 2003;Thomas, 2002;Xie & Ke, 2011); however, only one mixed-methods study (Exter et al, 2009) was found during the search, indicating a potential direction for future research. In many recent studies, social network analysis was applied to generate findings from a new perspective.…”
Section: Methods Appliedmentioning
confidence: 99%
“…Similar and complementary findings from multiple studies conducted in various contexts were compared and connected. For example, 12 studies reported to varying degrees that the online discussion being examined began with low-to medium-level interactions while higher level interactions were observed in the later stage of the discussions (Akarasriworn & Ku, 2013;Davidson-Shivers et al, 2000;Fernandez, 2007;Gerbic, 2006;Im, 2004;Jeong, 2003;Larson & Keiper, 2002;Mäkitalo et al, 2002;Poole, 2000;Sorensen & Baylen, 2004;Thomas, 2002;Xie & Ke, 2011). A closer examination of the contexts of these studies revealed that these 12 studies spanned a 14-year range, from 2000 to 2013, in four different countries with undergraduate and graduate students in five different academic disciplines.…”
Section: Holistic Representation Of the Participants' Interactionsmentioning
confidence: 99%
See 3 more Smart Citations